2018
DOI: 10.1007/978-3-319-73411-8_1
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Art Review of Curve Squeal Noise: Phenomena, Mechanisms, Modelling and Mitigation

Abstract: Curve squeal is an intense tonal noise occurring when a rail vehicle negotiates a sharp curve. The phenomenon can be considered to be chaotic, with a widely differing likelihood of occurrence on different days or even times of day. The term curve squeal may include several different phenomena with a wide range of dominant frequencies and potentially different excitation mechanisms. This review addresses the different squeal phenomena and the approaches used to model squeal noise; both time-domain and frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 86 publications
2
16
0
Order By: Relevance
“…Field measurements of squeal noise have also been carried out by a number of researchers [5]. It was found that the occurrence of curve squeal was more frequent on the inner wheel [1,24,[26][27][28]; however the outer wheel was also found to squeal in some cases [27,29].…”
Section: Several Laboratory Measurements Of Squeal Noise and Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field measurements of squeal noise have also been carried out by a number of researchers [5]. It was found that the occurrence of curve squeal was more frequent on the inner wheel [1,24,[26][27][28]; however the outer wheel was also found to squeal in some cases [27,29].…”
Section: Several Laboratory Measurements Of Squeal Noise and Frictionmentioning
confidence: 99%
“…This increases from zero with increasing creepage until it reaches saturation, at which point there is slip in the whole contact area and gross sliding occurs [4]. In some cases, for large creepages, the adhesion coefficient can decrease with further increase of creepage and the friction-creepage curve can thereby exhibit a negative slope [5].…”
Section: Introductionmentioning
confidence: 99%
“…A typical NS-intercity wheel used in the Dutch railway was measured. Because material damping of a wheel is generally very low and the exact value of the wheel modal damping is not critical for noise prediction [22] , the wheel dynamic behavior can be characterized by the modes and the corresponding natural frequencies [21,30] . The wheel modes are generally characterized by the numbers of nodal diameters and nodal circles [22] .…”
Section: Validation Of Wheel Dynamic Behaviormentioning
confidence: 99%
“…The simplifications of the point contact models and Kalker's contact models with discretized contact surface (widely used in the existing squeal prediction models) have unknown influences on the prediction of friction-induced vibration [20] . As reported by a recent review of the squeal study [21] , although Kalker's contact models can treat steady-state creepage, more detailed contact models that include transient effects may be needed for a correct representation of the squeal mechanisms.…”
Section: Introduction To Friction-induced Squealmentioning
confidence: 99%
“…A number of authors have proposed an alternative mechanism based on 'mode coupling', which has been explained in a simplified form by Hoffmann et al [24,25], see also [26]. More recently Thompson comprehensively reviewed two mechanisms ('falling friction' and 'mode coupling'), experimental and theoretical work in the field of curve squeal and discussed mitigation measures in terms of these two mechanisms [27].…”
Section: Introductionmentioning
confidence: 99%